Efeito do laser ER:YAG e ponta diamantada na morfologia da camada híbrida obtida com um adesivo autocondicionante: resistência de união ao microcisalhamento análise por MEV e MLCF - Gonçalves, Aline de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This study aims to evaluate the effect of Er: YAG (L) and bur (B) on the strength of resistance microshear (MPa) and the effect on the interface adhesive stickers and wash conditions (CL) - Adper Scotchbond Multipurpose and self (CS) - Adper EasyOne, both from 3M ESPE. Were formed 4 groups according tools and adhesives: B_CL (control); B_CS; L_CL and L_CS. 60 bovine incisors were randomly divided into experimental and groups: 40 to force microshear resistance (n = 10) and 20 for the adhesive interface morphology (6 to measure the thickness of the hybrid layer (CH) and length of tags (t) by MLCF (n = 3); 12 to the adhesive interface morphology by SEM (n = 3) and 2 to illustrate the effect of the instruments on dentine by SEM (n = 1). Microshear For testing four cylinders were fabricated composite Filtek Z350 XT - 3M ESPE (0.7 mm in diameter and 1 mm in height and area of adhesion of 0.38 mm) on each dentin surface treated by tools and adhesives. Testing of bond strength was performed in microshear FDMS universal testing machine 2000 with a load cell of 500 kgf and a speed of 0.5 mm / min. Adhesive interface was characterized by layer thickness hybrid (HC) and length of tags (t) in nm, with software UTHSCSA ImageTool. Values of bond strength to microshear L_CL were 34.10 ± 19.07, 24.26 ± 9.35 B_CL, L_CN 33.18 ± 12.46, 21.24 ± 13.96 B_CN. Anova two- way resulted in statistically significant only for instruments (p = 0.047). Mann-Whitney identified instruments to determine significant differences CH thickness and length (t). adhesives for these differences were only observed for (t). It can be concluded that 1) Laser Er: YAG results in higher bond strength to the microshear, regardless of the adhesive system (CL and CS). 2) The tags have no significant effect on bond strength to microshear. 3) The adhesive interface is affected by both instruments for cavity preparation and the type of adhesive system...

Este estudo tem como objetivo avaliar o efeito de laser de Er: YAG (L) e ponta diamantada (B) sobre a força de resistência ao microcisalhamento (MPa) e o efeito sobre a interface adesiva de adesivos condiciona e lava (CL) – Adper Scotchbond Multiuso e autocondicionante (CS) – Adper EasyOne, ambos da 3M ESPE. Foram constituídos 4 grupos segundo instrumentos e adesivos: B_CL (controle); B_CS; L_CL e L_CS. 60 incisivos bovinos foram randomicamente divididos nos experimentos e grupos: 40 para força de resistência ao microcisalhamento (n=10) e 20 para morfologia da interface adesiva (6 para mensuração da espessura da camada hibrida (CH) e comprimento de tags (t) por MLCF (n=3); 12 para morfologia da interface adesiva por MEV (n=3) e 2 para ilustração o efeito dos instrumentos sobre dentina por MEV (n=1). Para o ensaio de microcisalhamento foram confeccionados 4 cilindros de resina composta Filtek Z350 XT – 3M ESPE (0,7 mm de diâmetro por 1 mm de altura e área de adesão de 0,38 mm2) sobre cada superfície de dentina tratada pelos instrumentos e adesivos. O ensaio de resistência de união ao microcisalhamento foi realizado em máquina de ensaio universal EMIC 2000, com célula de carga de 500 Kgf e velocidade de 0,5 mm/min. A interface adesiva foi caracterizada pela espessura da camada hibrida (CH) e comprimento de tags (t) em μm, com o software UTHSCSA Imagetool. Os valores de resistência adesiva ao microcisalhamento foram L_CL 34,10 ± 19,07 MPa, B_CL 24,26 ± 9,35 MPa, L_CN 33,18 ± 12,46 MPa, B_CN 21,24 ± 13,96 MPa. Anova two-way resultou em diferença estatisticamente significativa somente para instrumentos (p=0,047). Teste de Mann-Whitney identificou os instrumentos determinam diferenças significativas para de espessura de CH e comprimento de (t). Para adesivos estas diferenças só foram observadas para (t). Pode-se concluir que 1) Laser de Er:YAG resulta em maiores valores de...
Keywords: Microscopia confocal; Lasers; Microscopia eletronica de varredura; Camada de esfregaço; Adesivos dentinários; Confocal microscopy